A Hub-based University Innovation Model - Prieto Mejia, Samuel; Montes Hincapie, Juan Manuel; Taborda Giraldo, John Alexander; Prieto Mejia, Samuel; Montes Hincapie, Juan Manuel; Taborda Giraldo, John Alexander (Journal of technology management & innovation, 2019)
This article uses a conceptual approach to propose an innovation model for regional universities. It demonstrates that the traditional university encounters several obstacles that hinder its full integration into the development of its respective region and explains why currently known models cannot adapt to regions that have deficient relationships with the government and lack an entrepreneurial base. The new model is based on a structure composed of units called “innovation hubs” and incorporates social innovation, thus permitting the university to become integrated into the regional innovation ecosystems. The Magdalena University in Colombia was used as a reference in developing the model. Keywords: hub; social innovation; university innovation models; regional innovation ecosystems
Keywords: Amérique latine; Colombie; Innovation sociale; Libre accès; Modèle; Partenariat; Pôle d'innovation; Rôle des universités; Université

A Hub-based University Innovation Model - Prieto Mejia, Samuel; Montes Hincapie, Juan Manuel; Taborda Giraldo, John Alexander; Prieto Mejia, Samuel; Montes Hincapie, Juan Manuel; Taborda Giraldo, John Alexander (Journal of technology management & innovation, 2019)
This article uses a conceptual approach to propose an innovation model for regional universities. It demonstrates that the traditional university encounters several obstacles that hinder its full integration into the development of its respective region and explains why currently known models cannot adapt to regions that have deficient relationships with the government and lack an entrepreneurial base. The new model is based on a structure composed of units called “innovation hubs” and incorporates social innovation, thus permitting the university to become integrated into the regional innovation ecosystems. The Magdalena University in Colombia was used as a reference in developing the model. Keywords: hub; social innovation; university innovation models; regional innovation ecosystems
Keywords: Amérique latine; Colombie; Innovation sociale; Libre accès; Modèle; Partenariat; Pôle d'innovation; Rôle des universités; Université